Global Domestic Workers Intersectional Inequalities and Struggles for Rights. - Marchetti, Sabrina (Bristol University Press, 2021)
EPDF and EPUB available Open Access under CC-BY-NC licence. Drawing from the EU-funded DomEQUAL research project across 9 countries in Europe, South America and Asia, this comparative study explores the conditions of domestic workers around the world and the campaigns they are conducting to improve their labour rights.